Writing the (Hamza) at the beginning of a Word in the Inscriptions of Makkah and Madinah during the First Two Hijri Centuries - Aloufi , Sultan (Dirasat: Human and Social Sciences, 2022)
This research presented the rulings of the Leading Hamza in Alphabet, writing and inscriptions of Makkah and Madinah in the first and the second centuries of Hijri. The research clarified its rulings in accordance with descriptive method, comparing it with what was scribed in the Holy Quran and well-known rulings of Alphabet and dictation. The research delved on The Leading Hamza’s general rulings which assimilated the description of its rules and roles in the words that it leads. Moreover it conjured up the changes that may occur sometimes to The Leading Hamza and takes it from the front to the middle, as it exposed some specific rulings of some words, like: a son, a daughter and a name.